Membangun Minat Berwirausaha Melalui Kegiatan Learning, Sharing & Practice - Wahyudi Wahyudi; Endang Sugiarti; Mukrodi Mukrodi; Rendi Salam; Samsul Anwar (Jurnal PKM Manajemen Bisnis, 2021)
Being a businessman is not easy, and does not happen by itself, it takes study and practice hard. In fact, it takes an environment and a mentor. Seeing this situation, as a lecturer is obliged to convey knowledge and foster the surrounding community, in order to improve intelligence and standard of living, one of which is through the implementation of entrepreneurship training. Explicitly, this activity aims to increase public knowledge and enthusiasm for business interests, so that life problems can be overcome. The scientific effort made is using a qualitative approach. Namely providing business training through methods of sharing knowledge, sharing business experiences, and business practices. Participants are the community in the Reni Jaya Rt. 009/014 Pondok Benda Pamulang. Descriptively, the results of the activity showed that the participants were enthusiastic about learning entrepreneurship. In addition, sharing business experiences can spark participants' enthusiasm for a business.